Digital knowledge generation and the appropriability trade-off. Issue 10 (November 2017) - Antonelli, Cristiano
Abstract: The introduction of information and communication technologies (ICT) has changed in depth the organization of the generation of knowledge reducing significantly knowledge absorption cost and improving knowledge interactions. The digital generation of knowledge relies on the systematic access and use of the stock of quasi-public knowledge. ICT enable to reconsider the knowledge appropriability trade-off as it helps to better appreciate the positive role of knowledge spillovers in the recombinant generation of new knowledge, next to the well-known negative effects of the limited appropriability of knowledge on revenues and hence incentives to innovate. This new analytical framework calls for an augmented role of telecommunications policy that should take into account the positive effects of knowledge connectivity on the generation of knowledge. Highlights: Knowledge appropriability has both positive and negative effects. Knowledge spillovers favor the reduction of knowledge costs. Limited appropriability affects the knowledge derived demand so as to reduces the incentives to perform r&d activities. The use of ict changes the generation of knowledge and favors the dissemination of knowledge and increases the net positive effects of limited appropriability. The new digital knowledge generation is enhanced by a new augmented telecommunications policy aimed to supporting the dissemination of knowledge and its access as an input.